Targeting phosphoinositide 3-kinase γ to fight inflammation and more - Barberis, Laura; Hirsch, Emilio (Thrombosis and Haemostasis, 2008)
The family of class I phosphoinositide-3-kinase (PI3K) is composed of four lipid kinases involved at multiple levels in innate and adaptive immune responses. Class I PI3Ks are divided into two subclasses, IA and IB, sharing a similar catalytic core. Whereas class IA PI3Ks are primarily activated by receptor tyrosine kinases, the unique element of class IB PI3K (PI3Kγ) is activated by G protein coupled receptors (GPCRs), like chemokine receptors. PI3Kγ is mainly expressed in leukocytes where it plays a significant role in chemotaxis. Here, we report recent advances in the analysis of the role of PI3Kγ in leukocytes and in endothelial cells. Results, derived from studies based on both pharmacological and genetic approaches, confirm PI3Kγ as an attractive target for drug discovery. PI3Kγ specific inhibition has gained increasing attention for the treatment of allergic, autoimmune and inflammatory diseases. Development of inhibitors has already provided series of hits, whose efficacy is currently under scrutiny worldwide.
Keywords: Inflammation; leukocyte trafficking / recruitment; signal transduction; endothelial cells